Retinopathy diseases screening system based on enhanced image processing algorithms / Hadzli Hashim - Hashim, Hadzli; Syed Adnan, Syed Farid; Mahyudin, Miswanudin Muizudin (2014)
Original Objectives as Proposed: 1. To investigate various image enhancing algorithms that can be used for retinopathy signature characterization of optic disk, blood vessels and lesions which include image filtering, image segmentations, edge detection and morphological techniques. 2. To formulate degree of retinopathy severity index based on image processing for lesions parameters and developing a friendly Graphical User Interface vision system that can aid ophtalmologists in giving decision for early detection.